Impact Of BCR-ABL1 Monitoring Among Patients With BCR-ABL1-Positive B-Acute Lymphoblastic Leukemia - Chong Siew Lian
Acute lymphoblastic leukaemia (ALL) with BCR-ABL1 confers a high risk of relapse and a poor prognosis. Access to the tyrosine kinase inhibitor as part of the treatment strategy has changed the risk stratification for ALL patients harbouring this fusion gene. As BCR-ABL1 is routinely quantified for the monitoring of its myeloproliferative counterpart, incorporation of its quantification by real-time polymerase chain reaction could be a reliable parameter for the monitoring of measurable residual disease (MRD) for ALL with BCR-ABL1. Whether this has replaced conventional risk factors in deciding whether patients would need a transplant or not is yet to be determined. This study aimed to determine the impact of BCR-ABL1 monitoring in patients with ALL with BCR-ABL1 on their outcome after allogeneic stem cell transplantation. We retrospectively analysed the survival outcome of these patients based on the quantification of BCR-ABL1 at three time-points; time-point 1 at the end of induction, time point 2 at post-consolidation week 16, and time point 3 at the end of treatment for patients who were transplant-eligible or nontransplant eligible. From 2006 to 2018, a total of 96 adult patients newly diagnosed with acute lymphoblastic leukemia with BCR-ABL1 were treated with chemotherapy and a tyrosine kinase inhibitor. Thirty-eight (41.3%) achieved overall remission; 33 patients underwent an allogeneic stem cell transplant. Our data showed that residual disease monitoring by real-time quantitative polymerase chain reaction performed prior to transplantation showed the highest survival correlation in ALL with patients with BCR-ABL1, especially for those who underwent allogeneic stem cell transplantation. Patients with MRD negative before transplantation had better survival compared to those who were MRD positive and showed excellent long-term outcomes after allogeneic stem cell transplantation. With the emergence of tyrosine kinase inhibitors and the incorporation of stringent, measurable residual disease monitoring, risk stratification for ALL with BCR-ABL1 has changed significantly.